Effect of Conscious Sedation vs. General Anesthesia on Outcomes in Patients Undergoing Mechanical Thrombectomy for Acute Ischemic Stroke: A Prospective Randomized Clinical Trial - Ren, Chunguang; Xu, Guangjun; Liu, Yanchao; Liu, Guoying; Wang, Jinping; Gao, Jian (Frontiers in Neurology, 2020)
Background: Although several studies have compared conscious sedation (CS) with general anesthesia (GA) in patients undergoing mechanical thrombectomy (MT), there has been no affirmative conclusion. We conducted this trial to assess whether CS is superior to GA for patients undergoing MT for acute ischemic stroke (AIS). Methods: AIS patients with anterior circulation large vascular occlusion (LVO) were randomized into two groups. The primary outcome was modified Rankin scale [mRS] score (0–2) at 90d after stroke. Secondary outcomes included intraprocedural hemodynamics, time metrics, successful recanalization, neurointerventionalist satisfaction score, National Institute of Health Stroke Scale (NIHSS) score, and Alberta Stroke Program Early CT Score (ASPECTS) at 48 h post intervention, mortality at discharge and 3 months after stroke, and complications. Results: Compared with the CS group, heart rate was significantly lower at T1–T8 in the GA group except at T4 (P<.05). Mean arterial pressure (MAP) and systolic blood pressure (SBP) were significantly lower in the GA group at T4–T6 and T9 (P<.05). Pulse oxygen saturation was significantly higher at T2–T9 in the GA group (P<.05). There were no significant differences in time metrics, vasoactive drug use, occurrence of >20% fall in MAP, pre-recanalization time spent with >20% fall in MAP, neurointerventionalist satisfaction, successful recanalization rate, NIHSS and ASPECTS scores at 48 h post intervention, and mortality rate at discharge and 3 months after stroke (P>.05). The cerebral infarction rate at 30d was greater in the CS group, but not significantly (P>.05). There were no differences in complication rates except for pneumonia (P>.05). Conversion rate from CS to GA was 9.52%. Conclusion: Anesthetic management with GA or CS during MT had no differential impact on the functional outcomes and mortality at discharge or 3 months after stroke in AIS patients, but CS led to more stable hemodynamics and lower incidence of pneumonia.